Investigation of skin self-examination and sunscreen use in adolescents in northern Cyprus - KAPTANOĞLU, ASLI FERİDE (TERMEDIA PUBLISHING HOUSE LTD, 2021)
Introduction: Regular skin self-examination (SSE) is very important for the early diagnosis of malignant melanoma (MM). Since sun exposure is the most important trigger factor for the development of skin cancers, effective and regular sun protection is the main preventive method. Aim: To investigate the awareness of SSE, risky nevus and sun protection of the adolescents in the Turkish Republic of Northern Cyprus (TRNC). Material and methods: The data used within this research were obtained from questionnaires administered to volunteer high school students in the TRNC. Results: 39.8% of the participants included in the study stated that they conducted SSE. All the participants who said they conducted SSE reported that they performed a face exam. The body regions that the participants did not examine were the scalp (47.7%), foot (36.9%), back (35.4%) and genital area (35.4%). The features of the nevus perceived by the participants as risk factors included rapid growth, bleeding and itching. While 74% of respondents said they used sunscreen products, only 9% of users reported using them every day. Conclusions: In the TRNC where the exposure to the sun is high, young people perform skin examinations at high rates in order to monitor their nevi. Nevertheless, the results of this research show that hard-to-reach areas are neglected.
Keywords: nevus; melanoma; skin self-examination; HIGH-RISK; CUTANEOUS MELANOMA; POPULATION; PREVALENCE; AWARENESS